Immediate and Sustained Effects of Cobalt and Zinc-Containing Pigments on Macrophages - Devcic, Julie; Dussol, Manon; Collin-Faure, Véronique; Pérard, Julien; Fenel, Daphna; Schoehn, Guy; Carrière, Marie; Rabilloud, Thierry; Dalzon, Bastien (Frontiers in Immunology, 2022)
Pigments are among the oldest nanoparticulate products known to mankind, and their use in tattoos is also very old. Nowadays, 25% American people aged 18 to 50 are tattooed, which poses the question of the delayed effects of tattoos. In this article, we investigated three cobalt (Pigment Violet 14 (purple color)) or cobalt alloy pigments (Pigment Blue 28 (blue color), Pig-ment Green 14 (green color)), and one zinc pigment (Pigment White 4 (white color)) which con-stitute a wide range of colors found in tattoos. These pigments contain microparticles and a sig-nificant proportion of nanoparticles (in either aggregate or free form). Because of the key role of macrophages in the scavenging of particulate materials, we tested the effects of cobalt- and zinc-based pigments on the J774A.1 macrophage cell line. In order to detect delayed effects, we com-pared two exposure schemes: acute exposure for 24 hours and an exposure for 24 hours fol-lowed by a 3-day post-exposure recovery period. The conjunction of these two schemes allowed for the investigation of the delayed or sustained effects of pigments. All pigments induced func-tional effects on macrophages, most of which were pigment-dependent. For example, Pigment Green 19, Pigment Blue 28, and Pigment White 4 showed a delayed alteration of the phagocytic capacity of cells. Moreover, all the pigments tested induced a slight but significant increase in TNF secretion. This effect, however, was transitory. Conversely, only Pigment Blue 28 induced a short and sustained increase in interleukin 6. Results showed that in response to bacterial stim-uli (LPS), the secretion of tumor necrosis factor and interleukin 6 declined after recovery expo-sure with pigments. The pigments also induced persisting changes in some important macro-phage membrane markers such as CD11b, an integrin contributing to cell adhesion and immu-nological tolerance. In conclusion, the pigments induced functional disorders in macrophages, which, in some cases, persist long after exposure, even at non-toxic doses.